Single-Virus Droplet Microfluidics for High-Throughput Screening of Neutralizing Epitopes on HIV Particles. Issue 6 (22nd June 2017) - Chaipan, Chawaree; Pryszlak, Anna; Dean, Hansi; Poignard, Pascal; Benes, Vladimir; Griffiths, Andrew D.; Merten, Christoph A.
Summary: Analyzing surface epitopes of single HIV particles holds great potential for the development of vaccine candidates. However, existing technologies do not allow corresponding screens at high throughput. We present here a single-virus droplet-based microfluidics platform enabling sorting of millions of HIV-1 particles with >99% efficiency, based on the expression of epitopes recognized by broadly neutralizing antibodies. We show that virus particles displaying these epitopes can be identified, sorted, and analyzed by next-generation sequencing: an approximately 1, 900-fold enrichment of viral particles displaying neutralizing epitopes could be obtained in a single sort, thus opening the way for screening diverse virus libraries with optimal antigenic features for HIV vaccine candidates. Graphical Abstract: Highlights: High-throughput system for the screening of vaccine candidates Millions of parallelized single-virus assays HIV-1 particles displaying epitopes of interest can be sorted with >99% efficiency Abstract : Chaipan, Pryszlak et al. have established a high-throughput droplet-based microfluidics platform to screen and sort millions of single virus particles for optimal antigenic features of vaccine candidates. This system allowed 1, 896-fold enrichment of target viral particles with a sorting efficiency above 99%.